Tailoring the rice starch for the application in food sector by different processes - Saadia Zainab; Xianqing Zhou; Yurong Zhang; Saira Tanweer; Tariq Mehmood (Food Physics)
Rice starch is of great importance due to its extensive use in the food industry. The main component of rice starch is carbohydrates with minute amounts of lipids and proteins. Due to the diverse aspects of native rice starch, there’s a need to improve the characteristics of rice starch to use them easily in the food sector. Many rice starch characteristics can be improved through different processes among which some of the improved properties are paste clarity, solubility, swelling power, gelatinization, retrogradation, starch structure, and rheology. These improvements can be done through physical modifications, chemical modifications, and emerging approaches. After modifications, the usage of rice starch in the food items can be efficiently increased. This paper mainly aims at the basic properties and their improvements through modifications making them applicable in the food sector. In short, the main properties of rice starch which can be improved through modification and its application in the food sector are explained in detail.